الحقائق الإنسانية في شخصية عبد الكريم بقصة "أرخص الليالي" ليوسف إدريس: دراسة في البنيوية الجينية عند لوسيان غولدمان: Human Realities in Abdul Karim’s Character in Yusuf Idris’s “Arkhas al-Layali” (“The Cheapest Nights”): A Genetic Structuralism Study - Mohammad Farhan Kholil; Andi Holilulloh; Fouad Larhzizer (LISANIA: Journal of Arabic Education and Literature, 2026)
This research analyzes the human realities represented in Abdul Karim’s character in Yusuf Idris’s short story “Arkhas al-Layali” (“The Cheapest Nights”) through Lucien Goldmann’s Genetic Structuralism framework. Using a qualitative descriptive method and close reading of the original Arabic text, the study examines the relationship between social and individual realities reflected in the character’s experiences. The findings show that structural poverty, unequal power relations, and oppressive social conditions shape Abdul Karim’s life, while his reflective awareness and symbolic resistance reveal individual agency and social consciousness. The analysis demonstrates that social structures do not fully determine individual consciousness, as the character continues to resist domination through language and imagination. Abdul Karim ultimately represents the worldview of the oppressed rural class in postcolonial Egyptian society. The study also highlights literary language as a medium for expressing social criticism and human suffering in Egyptian rural life, particularly through symbolic narration and psychological representation. Furthermore, the findings illustrate the close connection between literary structure and social reality in shaping the character’s worldview and existential struggles. This study confirms the relevance of Goldmann’s Genetic Structuralism in analyzing modern Arabic literature.